EFEKTIVITAS PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP HASIL BELAJAR MATA PELAJARAN IPS SMP - Kadir, Abdul; Aminuyati, Aminuyati; Ulfah, Maria (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was conducted based on the observation that learning carried out in classrooms on social studies subjects is always done using conventional learning models namely lectures and question and answer. This study aims to determine the effectiveness of the application of discovery learning learning models to learning outcomes in social studies subjects in class VII Bawari Islamic Middle School Pontianak. The method used is Quasi Experiment Design with the research design used is Nonequivalent Control Group Design. The sample of this study was 49 students. The results of data analysis showed that student learning outcomes between the experimental class and the control class experienced significant differences. Evidenced by the results of the post-test average in the control class treated with conventional learning models, namely 77.75. In the experimental class that was treated using the Discovery Learning learning model the average post-test score of students was increased by 82.5. This is directly proportional to the level of effect size obtained, which is equal to 0.71. This achievement is included in the high category. This means that there are significant differences in the learning outcomes of the experimental class and the control class.Â Keywords:Â  Effectiveness, Learning Model, Discovery learning, Learning Outcomes